Very Late Scaffold Thrombosis after Everolimus-Eluting Bioresorbable Scaffold Implantation in Patients with Unremarkable Interim Surveillance Angiography: Very late bioresorbable scaffold thrombosis - Hoppmann, Petra; Rai, Himanshu; Colleran, Roisin; Kufner, Sebastian; Wiebe, Jens; Cassese, Salvatore; Joner, Michael; Laugwitz, Karl -Ludwig; Kastrati, Adnan; Byrne, Robert A. (Cardiovascular Revascularization Medicine, 2020)
Purpose: Everolimus-eluting bioresorbable scaffolds (BRS) demonstrated an increased risk of very late scaffold thrombosis (VLScT) in comparison with conventional drug-eluting stents. However, characterization of VLScT cases remains scant and the role of interim angiographic surveillance in identifying patients at risk of VLScT is unclear. We therefore set out to identify angiographic predictors of VLScT in our present case series. Methods: We analyzed a series of consecutive patients with VLScT presenting to two centers in Munich, Germany. Of interest, all patients had undergone interim planned surveillance angiography. Angiographic films were collected and reviewed and quantitative coronary angiography analysis was done at a core laboratory. Optical coherence tomography (OCT) images at presentation with VLScT were analyzed in patients with available data. Results: Nine patients presented with 10 VLScT events. Mean age was 62.6 years. Surveillance angiography (between 159 and 476 days) were unremarkable in all cases. Time from index intervention to VLScT ranged from 393 to 1494 days. Nine of 10 events occurred after discontinuation of dual antiplatelet therapy. Four patients underwent OCT. The dominant finding at the time of VLScT was scaffold discontinuity. Conclusions: In a series of patients with VLScT after treatment with BRS, routine interim surveillance angiography was available in all patients and failed to identify features predictive of subsequent adverse events.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bioresorbable scaffolds; Optical coherence tomography; Quantitative coronary angiography; Very late scaffold thrombosis